To find the derivative of a composite function we use the chain rule
![f(g(x))^(\prime)=f^(\prime)(g(x))g^(\prime)(x)](https://img.qammunity.org/2023/formulas/mathematics/college/wzsaormed6fw0fmawh1blup9jgoce24rgx.png)
Then, we first find the derivatives of f and g. The function f is of the form
![\begin{gathered} (d)/(dx)u^a=au^(a-1)(du)/(dx) \\ u=x^2-3 \\ a=(1)/(2) \\ (du)/(dx)=2x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/57nhdlz8sk52rk8nv2blcoss91qc2z662a.png)
Then
![f^(\prime)(x)=(1)/(2)(x^2-3)^(-1/2)(2x)=\frac{x}{\sqrt[]{x^2-3}}](https://img.qammunity.org/2023/formulas/mathematics/college/ghiuuh6cyjnyfmlo9b8lhyhfgauy1c2zlm.png)
On the other hand, the derivative of g is very simple
![g^(\prime)(x)=4](https://img.qammunity.org/2023/formulas/mathematics/college/df8p0dntj1e5g72prsego9calj9oqbcz35.png)
After doing this, we evaluate f' in g(x), and we have
![f^(\prime)(g(x))=\frac{4x-2}{\sqrt[]{(4x-2)^2-3}}](https://img.qammunity.org/2023/formulas/mathematics/college/xlc6fdvc37rb8m8lzmh8khll1nl6xqe0in.png)
Replacing f'(g(x)) and g'(x) we obtain
![f(g(x))^(\prime)=f^(\prime)(g(x))g^(\prime)(x)\text{ = }\frac{4x-2}{\sqrt[]{(4x-2)^2-3}}\cdot4](https://img.qammunity.org/2023/formulas/mathematics/college/2evdbmfbpj43gt7q3jmjc2o745b8uowdk6.png)
Finally, we evaluate this expression in x=1
![(f\circ g)^(\prime)(1)=4\frac{4(1)-2}{\sqrt[]{(4(1)-2)^2-3}}=4\cdot\frac{2}{\sqrt[]{2^2-3}}=(8)/(1)=8](https://img.qammunity.org/2023/formulas/mathematics/college/umqhndh5u83skx2k0ukqllllbulop4fnlj.png)
Then, the answer is 8